Discussion on "Modeling karst spring hydrograph recession based on head drop at sinkholes" by Guangquan, Li, Nico Goldscheider, Malcom S. Field - Şen, Zekai (Elsevier Science Bv, 2018)
Groundwater movement model development in karstic aquifers is very difficult due to the complexity of the solution cavities. The authors (Li et al., 2016) have proposed a square law model for expressing the discharge ratio in terms of hydraulic head ratio, with an exponent equal to 0.5. They have also provided the mathematical derivation in detail with application. It is noticed that the methodology can be expanded towards a better and refined solutions by consideration of the following explanations.
WOS: 000425077300001
Keywords: Malcom S. Field; Nico Goldscheider; Karst Spring Hydrograph